(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
In many respects, it can be recognized that this is due to the natural geographic changes taking place in the Central Asian region in recent years and, as a result of its degradation, causes the formation of various biological, morphological and ecological-physiological signs and characteristics in plants. species growing in natural conditions in the northern regions of our republic.